Prevalence of Toxoplasma gondii and Toxocara canis among Patients with Uveitis. (October 2014) - Lim, Su Jin; Lee, Sang Eun; Kim, Sun Hyun; Hong, Sung-Hee; You, Yong Sung; Kwon, Oh Woong; Kim, Hyeun Seung
Abstract Purpose: To investigate the prevalence of Toxoplasma gondii and Toxocara canis in patients with uveitis. Method: Patients with uveitis were examined. Serum antibodies to T. gondii and T. canis were tested by using enzyme-linked immunosorbent assay (ELISA). Polymerase chain reaction (PCR) was done using blood and aqueous humor (AH). Results: 98 patients were enrolled. Mean age was 43.5 ± 13.2 years. Six patients were seropositive for T. gondii with the following pattern—anterior uveitis: 1; posterior uveitis with retinitis: 2; pan uveitis: 2. One patient had a positive result of PCR for T.gondii in AH, who showed pan uveitis. 23 patients were positive to serum IgG for T. canis with the following clinical manifestation—granuloma: 6; pigmented scar: 3; virtrits: 6—but none were PCR positive. Conclusion: T.gondii and T.canis are still one of the important causes of uveitis. Ocular toxocariasis is not an uncommon cause of uveitis even in adult.